THE REGULARITY OF DISTRIBUTION OF PHYSICOMECHANICAL PROPERTIES OF RECENT ALLUVIAL SEDIMENTS BY VOLGO-AKHTUBA FLOODLAND - Z. V. Kalashnik (Ûg Rossii: Èkologiâ, Razvitie, 2014)
The presented article considers the questions physico-mechanical characteristic soil recent alluvial sediments Volga-Akhtuba floodland in connection with designing and construction different industrial object, and first of all,oil-and-gas of the infrastructure.